Design of hybrid RO/NF permeate staging for the supply of clean water in Tanjung Lame Village. Issue 1 (January 2021) - Prayoga, Anton; Zakwan, Muhammad; Bismo, Setijo
Abstract: The groundwater sources from community wells in Tanjung Lame village, Pandeglang district, are very salty, so they are not suitable for consumption. Reverse osmosis (RO) and nanofiltration (NF) membrane are alternative desalination technologies for treating clean water from saltwater wells. However, the pressure required on a conventional single-stage RO filtration system is very high. The purpose of this study is to design a hybrid RO/NF filtration system that can operate at low pressure. The designed hybrid RO/NF permeate staging has proven to be able to produce clean water from saltwater wells in Tanjung Lame village at low pressure. To obtain optimum results, the designed hybrid RO/NF permeate staging is operated at the first and second stage pressure of 6 and 3 bar, respectively. At that pressure, the salt rejection and TDS of permeate is 97.06% and 85 ppm, respectively. The water recovery rate and permeate flow rate is 31% and 1.55 liters/minute, respectively.